The Buenos Aires Water Concession - Alcázar, Lorena (The World Bank, 1999)
April 2000 - Transparent, rule-based decisionmaking is important to maintaining public trust in regulated infrastructure. The Buenos Aires water and sanitation concession led to remarkable improvements in delivery and coverage of services and to lower prices for consumers. But a poor information base, lack of transparency in regulatory decisions, and the ad hoc nature of executive branch interventions make it difficult to reassure consumers that their welfare is being protected and that the concession is sustainable. The signing of a concession contract for the Buenos Aires water and sanitation system in December 1992 attracted worldwide attention and caused considerable controversy in Argentina. It was one of the world's largest concessions, but the case was also interesting for other reasons. The concession was implemented rapidly, in contrast with slow implementation of privatization in Santiago, for example. And reform generated major improvements in the sector, including wider coverage, better service, more efficient company operations, and reduced waste. Moreover, the winning bid brought an immediate 26.9 percent reduction in water system tariffs. Consumers benefited from the system's expansion and from the immediate drop in real prices, which was only partly reversed by subsequent changes in tariffs and access charges. And these improvements would probably not have occurred under public administration of the system. Still, as Alcázar, Abdala, and Shirley show, information asymmetries, perverse incentives, and weak regulatory institutions could threaten the concession's sustainability.